Estructura y variación estacional de poblaciones de moluscos asociadas a la pesca artesanal de langosta en el Pacífico Tropical - Olabarria, Celia (Revista de Biología Tropical, 1999)
Mollusks associated to the spiny lobster fishery during 1997-1998 in the Tropical Pacific were surveyed. A total of I 081 specimens of 11 species were collected. The greatest captures were in autumn 1997 (28.16%) and surnmer 1998 (25.58%). Dominant species were Hexaplex nigritus (Philippi 1845) (83.10%), Chicoreus regius (Swainson 1821) (8.04%), Vasum caestus (Broderip 1833) (2.12%), C. brassica (Lamarck 1822) (1.85%) and C. erythrostomus (Swainson 1831) (1.75%), which have commercial importance. Weight-height ratio, sex ratio and height frequency hislograms were done for dominant species. Sex ratio was 1: 1, exc';pt for C. erythrostomus and H. nigritus (2 males: I female); C. regius, C. el),throstomus and V. caestlis presented an allometric growth while H. nigritlls and C. brassica grew isometricaIly. Only H. nigritus males were larger than conspecitlc females. T here were significative differences in species dístribution in relation with depth; C. erythrostomus occurred in deepest layers while H. nigritus was more superficial; H. nigritus size differed with depth, temperature and localily.